Effect of Bacillus amyloliquefaciens as a Probiotic on Growth Performance Parameters of Pitalah Ducks - Zurmiati; Wizna; Abbas, M. Hafil; Mahata, Maria Endo; Fauzano, Revan (International Journal of Poultry Science, 2017)
Background and Objective: Live probiotic feed additives can balance microorganism populations in the digestive tract. This study aimed to investigate the effects of the probiotic Bacillus amyloliquefaciens on growth performance and feed efficiency of Pitalah starter ducks. Methodology: A completely randomized design was used in this study. Three different doses of B. amyloliquefaciens (1000, 2000 and 3000 ppm) were dispensed in the drinking water of 1 day old Pitalah ducks (N = 25 duck per dose) and each treatment was replicated five times, control birds were given 0 ppm (N = 25 duck). Feed consumption and conversion, body weight gain, income over feed cost, total colony count of Bacillus sp., in the small intestines and acidity in small intestine were measured. Results: The results showed that all three doses significantly decreased feed consumption, feed conversion and small intestinal acidity (p0.05). Conclusion: It is concluded that addition of 2000-3000 ppm of B. amyloliquefaciens to the drinking water of Pitalah ducks can improve the feed efficiency by >15% and provide economic benefits for farmers raising starter ducks.